Postconcussion Symptoms After an Uncomplicated Mild Traumatic Brain Injury in Older Adults: Frequency, Risk Factors, and Impact on Quality of Life. Issue 5 (25th September 2022) - Chung, Jia-Wei; Liu, Doresses; Wei, Li; Wen, Ya-Ting; Lin, Hsin-Ying; Chen, Huan-Chieh; Chiu, Hsiao-Yean
Abstract : Background: Postconcussion symptoms (PCSs) are common complaints reported by patients after a mild traumatic brain injury (TBI), and these symptoms may lower quality of life. Previous investigations have primarily focused on PCSs in children, adults, and athletes. The frequency, and risk factors, and effects of PCSs for older adults with mild TBIs are unclear. Purpose: To investigate the frequency and risk factors of PCSs, and investigate their effects on quality of life over time after mild TBI in older adults. Methods: A prospective longitudinal study was performed. All participants were enrolled from the emergency department or neurosurgical outpatient clinics of a medical center. The measurement tools were the Rivermead Post-Concussion Symptoms Questionnaire and the Quality of Life after Traumatic Brain Injury. Measurements were performed on the seventh day, at the first month, and at the sixth month after the head injury. A generalized estimating equation model was used for data analyses. Results: One hundred and one older adults (mean age of 76.0 years) with mild TBIs with negative neuroimaging findings were included. Overall, 32.7%, 4%, and 15.8% of the sample reported PCS after 7 days, 1 month, and 6 months of head injury, respectively, revealing a U-shaped trend. We observed that comorbidity measured using the modified Charlson Comorbidity Index was associated with differences in PCSs ( P < .05). PCSs were an independent predictor of changes in postinjury quality of life ( P < .001). Conclusions: The results indicate that PCS after a mild TBI in older adults is prevalent, even in the chronic phase after a TBI, and PCSs significantly affected the quality of life of our cohort. Therefore, to improve patient quality of life, healthcare providers should employ effective interventions to manage PCSs at different phases after a TBI.